Competition and adverse selection in the small-dollar loan market: Overdraft versus payday credit - Brian T. Melzer; Donald P. Morgan (Federal Reserve Bank of New York, 2009)
We find that competition from payday lenders leads depository institutions to raise overdraft fees and reduce the availability of 'free' checking accounts. We attribute this rise in prices partly to adverse selection created by banks' practice of charging a flat fee regardless of the overdraft amount - pricing that favors depositors prone to large overdrafts. Payday credit is priced per dollar borrowed, so when that option is available, depositors prone to small overdrafts switch. That selection works against banks; large overdrafts cost more to supply and, if depositors default, banks lose more, so prices rise. Consistent with this adverse selection hypothesis, we document that the average dollar amount per returned check at banks and other depository institutions increases when depositors have access to payday credit. Our findings illuminate competition and pricing frictions in the large, yet largely unstudied, small-dollar loan market.
Keywords: G21; G20; D14; 330; Payday credit; overdraft credit; competition; adverse selection